Chlorogenic Compounds from Coffee Beans Exert Activity against Respiratory Viruses - Sinisi, Valentina; Stevaert, Annelies; Berti, Federico; Forzato, Cristina; Benedetti, Fabio; Navarini, Luciano; Camps, Anita; Persoons, Leentje; Vermeire, Kurt (Planta Medica, 2017)
Chlorogenic acids are secondary metabolites in diverse plants. Some chlorogenic acids extracted from traditional medicinal plants are known for their healing properties, e.g., against viral infections. Also, green coffee beans are a rich source of chlorogenic acids, with 5-O-caffeoylquinic acid being the most abundant chlorogenic acid in coffee. We previously reported the synthesis of the regioisomers of lactones, bearing different substituents on the quinidic core. Here, 3,4-O-dicaffeoyl-1,5-γ-quinide and three dimethoxycinnamoyl-γ-quinides were investigated for in vitro antiviral activities against a panel of 14 human viruses. Whereas the dimethoxycinnamoyl-γ-quinides did not show any antiviral potency in cytopathogenic effect reduction assays, 3,4-O-dicaffeoyl-1,5-γ-quinide exerted mild antiviral activity against herpes simplex viruses, adenovirus, and influenza virus. Interestingly, when the compounds were evaluated against respiratory syncytial virus, a potent antiviral effect of 3,4-O-dicaffeoyl-1,5-γ-quinide was observed against both subtypes of respiratory syncytial virus, with EC50 values in the submicromolar range. Time-of-addition experiments revealed that this compound acts on an intracellular post-entry replication step. Our data show that 3,4-O-dicaffeoyl-1,5-γ-quinide is a relevant candidate for lead optimization and further mechanistic studies, and warrants clinical development as a potential anti-respiratory syncytial virus drug.
Keywords: chlorogenic acids; quinides; coffee; antiviral activity; influenza virus; respiratory syncytial virus